FORTIFIKASI TEPUNG TULANG IKAN NILA PADA FLAKY CRACKERS - nindya hendri; Rahmi Holinesti; Anni Faridah; Risma Rahmatunisa (Pasundan Food Technology Journal (PFTJ), 2026)
This study aimed to evaluate the effect of tilapia bone flour addition on the sensory quality of flaky crackers as a calcium-enriched functional food. An experimental approach using a Completely Randomized Design (CRD) was applied with four treatments: 0%, 5%, 10%, and 15% bone flour substitution, each in triplicate. Sensory evaluation was conducted by 30 untrained panelists using a hedonic scale to assess shape, color, aroma, texture, and taste. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test at a 5% significance level.The results indicated that bone flour addition had no significant effect on shape (fish-shaped, neatness, and uniformity), color, porous texture, and taste (p>0.05), but significantly affected aroma and crispness (p<0.05). Descriptively, the 10% treatment produced the most optimal shape and porous texture, while the 15% treatment resulted in the highest scores for color, crispness, and taste. However, increasing substitution levels tended to reduce aroma quality due to the presence of volatile compounds. In conclusion, tilapia bone flour can be incorporated up to 15% without significantly compromising sensory acceptability and may enhance the nutritional value, particularly calcium content. These findings highlight its potential as a sustainable fortification ingredient in value-added food products derived from fishery by-products.